Correlation of Serum Immunoglobulin A and Immunoglobulin A / Complement 3 Ratio with IgA Nephropathy: One Year Prospective Study - Mainali, Nirajan; Kshatree , Keshika (Journal of Nobel Medical College, 2024)
Background: IgA nephropathy is the most prevalent primary glomerulonephritis worldwide, characterized by the mesangial deposition of IgA immune complexes.Its clinical course is highly variable, ranging from indolent to rapidly progressive forms, and it represents a significant challenge in nephrology. The diagnostic potential of the IgA/C3 ratio, can provide valuable insights into the underlying immunological processes.Materials and Methods: This is a one year prospective study done in the department of renal pathology at Pratham pathology private limited during the period of 1st November 2021-30th October 2022. Data of all patients were evaluated for the histopathological diagnosis. Report of all cases were reviewed for prebiopsy report of serum IgA and C3 level. All cases of which serum IgA and C3 done were included for the study. Those cases, which didn’t perform serum IgA and C3, were excluded from the study.Results: A total of 182 cases of kidney biopsies were received for evaluation during this period. Out of it 22 cases (12.08 %) were those of IgA Nephropathy.  Of which, 13 patients had done a blood level of IgA and C3. There was no statistical difference between serum C3 level, IgA and/or IgA/C3 between IgA nephropathy and non IgA nephropathy.Conclusion: There is no significance variation between serum IgA, C3 and /or IgA/C3 level between IGA nephropathy and other glomerular diseases.